Impact of hemoglobin nitrite to nitric oxide reductase on blood transfusion for resuscitation from hemorrhagic shock - Chad Brouse; Daniel Ortiz; Yan Su; Bryan Oronsky; Jan Scicinski; Pedro Cabrales (Asian Journal of Transfusion Science, 2015)
Background: Transfusion of blood remains the gold standard for fluid resuscitation from hemorrhagic shock. Hemoglobin (Hb) within the red blood cell transports oxygen and modulates nitric oxide (NO) through NO scavenging and nitrite reductase. Aims: This study was designed to examine the effects of incorporating a novel NO modulator, RRx-001, on systemic and microvascular hemodynamic response after blood transfusion for resuscitation from hemorrhagic shock in a hamster window chamber model. In addition, to RRx-001 the role of low dose of nitrite (1 × 10−9 moles per animal) supplementation after resuscitation was studied. Materials and Methods: Severe hemorrhage was induced by arterial controlled bleeding of 50% of the blood volume (BV) and the hypovolemic state was maintained for 1 h. The animals received volume resuscitation by an infusion of 25% of BV using fresh blood alone or with added nitrite, or fresh blood treated with RRx-001 (140 mg/kg) or RRx-001 (140 mg/kg) with added nitrite. Systemic and microvascular hemodynamics were followed at baseline and at different time points during the entire study. Tissue apoptosis and necrosis were measured 8 h after resuscitation to correlate hemodynamic changes with tissue viability. Results: Compared to resuscitation with blood alone, blood treated with RRx-001 decreased vascular resistance, increased blood flow and functional capillary density immediately after resuscitation and preserved tissue viability. Furthermore, in RRx-001 treated animals, both mean arterial pressure (MAP) and met Hb were maintained within normal levels after resuscitation (MAP >90 mmHg and metHb <2%). The addition of nitrite to RRx-001 did not significantly improve the effects of RRx-001, as it increased methemoglobinemia and lower MAP. Conclusion: RRx-001 alone enhanced perfusion and reduced tissue damage as compared to blood; it may serve as an adjunct therapy to the current gold standard treatment for resuscitation from hemorrhagic shock.